Physical Properties of Guinea Corn Stalk Fibre Reinforced High-Density Polyethylene (HDPE) Composite for The Production of Particle Board - James, E.; Aji, I. S.; Dauda, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT)
Majority of developing nations view the construction/manufacturing sector as being crucial to their economy. The industry produces panels and boards for furniture, ceilings, panelling, and other wood-based manufactured projects, relying solely on forest resources. This heavy dependence strains forests, contributing to deforestation and causing prolonged damage to ecosystems. A major interest in finding substitute raw materials for the manufacture of boards and panels through the utilization of agricultural waste products, is becoming the direction to scholars. In this study, guinea corn stalk fibre reinforced high density polyethylene (HDPE) composite was developed and analysed for the production of Particle Board. The composites were produced through the process of compounding and compression moulding operation. The HDPE was varied from 100 - 50 Wt % at interval of 10 Wt % while the filler was reversed from 10 - 50 Wt % at interval of 10 Wt %. Five different composites samples were formulated using 250 μm fibre size using HDPE as binder and a 100 % HDPE as control sample. The physical (density, thickness swelling and water absorption) properties of the developed composite were evaluated. The density (ranges from 943.9 kg/m³ to 1075.5 kg/m³), thickness swelling (3.13% to 18.75%), and water absorption (0.28% to 2.01%) of all the composites increased with increasing filler loading with highest values obtained at 50 Wt % material loading. All the values are within the minimum requirement stipulated in the European standard EN 312:2010 for general purpose particle boards except for the density which is above the standard. The incorporation of the fillers into the HDPE matrix generally enhanced the physical properties of the matrix. The Guinea Corn Stalk Fibre (GCSF) composite produced with 60 Wt % matrix and 40 Wt % filler is the most suitable for general purpose particle board production as all the physical properties met the required standard stipulated in the European standard EN 312:2010 for general purpose particle board.